AKIBAT HUKUM PERJANJIAN KERJA WAKTU TERTENTU YANG DIBUAT TIDAK DENGAN BENTUK TERTULIS - Suartini, Sri; Walesa Putra, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014)
This paper shall be entitled as “Legal Implications of Periodical Contractual Unwritten Agreement (PKWT)". This paper shall apply normative legal research and statutory approach with the aims knowing the form of agreement and its unwritten legal implication. Contractual relationship existed among entrepeneur and employee shall be based upon working contract. It shall be made in either written or unwritten form. However, within the circumstances of such unwritten contract, such the contract shall be classified into Uncertain Periodical Agreement.
Keywords: Working Relationship, Periodical Contractual Agreement, Legal Implication